PENGARUH PEMAKAIAN BATUBARA LOW GRADE TERHADAP BIAYA PRODUKSI CLINKER DI PT SEMEN BATURAJA Tbk - Anggara, Putra; Bramana, Sally Maria; Mushoddiq, Achmad Johan (KOLEGIAL, 2024)
The aim of this research is to determine the effect of using low grade coal on clinker production costs at PTSemen Baturaja Tbk. The data analysis technique used is qualitative and quantitative data analysis. Theresearch method used in this research is descriptive. Based on the results of data processing, the simple linearregression equation obtained is Y=17456.390+1.956X. And the correlation value of 0.932 is in the position of0.800 – 1.000, so the relationship is stated to be very strong, while the coefficient of determination (R Square)value is 0.869 or 86.9%, this value shows that the contribution of the independent variable (low grade coal) is86.9 % of the dependent variable (clinker production costs), while the remaining 13.1% is the contribution ofother factors not studied. Based on the data obtained for the low grade coal variable (X), the partialsignificance test (t test) produces a tcount value of 15.030 > ttable of 2.032. So Ho is rejected and Ha isaccepted, so there is an influence of low grade coal (X) on clinker production costs (Y) at PT Semen BaturajaTbk.